2007
DOI: 10.1093/ecam/nen002
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture: What Underlies Needle Administration?

Abstract: Acupuncture is an ancient Chinese therapy with its mode of action unclear and efficacy inconclusive. A lack of attention given to the role of psychosocial context presented in clinical provision of acupuncture may mainly account for the current dilemma in acupuncture research. This psychosocial context induces various cognitive and affective processes in the patient while receiving this treatment. On the basis of the analysis of these psychological factors involved in clinical provision of acupuncture and in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 58 publications
1
31
0
1
Order By: Relevance
“…Thus, the lack of analgesia effect in the VL group by no means implies that acupuncture does not work, but rather indicates the importance of expectation in the treatment process. In fact, we believe this finding is consistent with the essence of Traditional Chinese Medicine (Liu, 2008). For instance, the oldest canonical classic of Chinese medicine, the Yellow Emperor’s Inner Classic ( Huang Di Nei Jing ) written in the first century BCE, states that, “if a patient does not consent to therapy [acupuncture] with positive engagement, the physician should not proceed as the therapy will not succeed” ( SuWen Chapter 11).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the lack of analgesia effect in the VL group by no means implies that acupuncture does not work, but rather indicates the importance of expectation in the treatment process. In fact, we believe this finding is consistent with the essence of Traditional Chinese Medicine (Liu, 2008). For instance, the oldest canonical classic of Chinese medicine, the Yellow Emperor’s Inner Classic ( Huang Di Nei Jing ) written in the first century BCE, states that, “if a patient does not consent to therapy [acupuncture] with positive engagement, the physician should not proceed as the therapy will not succeed” ( SuWen Chapter 11).…”
Section: Discussionsupporting
confidence: 86%
“…Acupuncture may be defined as the insertion of one or more needles into specific sites on the body surface for the purpose of treatment [19]. Neuroimaging studies investigating the acupuncture process have observed overlapping brain activations in the cortical sensorimotor and salient networks, as well as deactivations in the limbic-paralimbic neocortical network [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical effects of acupuncture treatment (e.g., analgesic effects) have been investigated and confirmed in a number of studies in animals and in clinical populations, and many researchers have contributed to identifying the brain processes activated by acupuncture [23]. Nevertheless, the underlying mechanisms of acupuncture and its mode of action are unclear, and psychosocial and contextual factors such as expectation, attention, and body schema may play important roles in the clinical effects of acupuncture [24]. However, no studies are available in which different aspects of bodily self-awareness have been actively manipulated and investigated.…”
Section: Introductionmentioning
confidence: 99%